Cell‐Laden Hydrogels in Integrated Microfluidic Devices for Long‐Term Cell Culture and Tubulogenesis Assays. Issue 18 (7th March 2013) - Gabrielson, Nathan P.; Desai, Amit V.; Mahadik, Bhushan; Hofmann, Marie‐Claude; Kenis, Paul J. A.; Harley, Brendan A. C.
<x xml:space="preserve">Abstract</x> A hydrogel biochip combining microfluidic mixing and orthogonal supplementation strategies is developed and validated to allow facile generation of libraries of optically transparent 3D culture microenvironments. Live, on‐chip tracing of embryonic stem cell differentiation and endothelial cell tubulogenesis confirms that the platform can be used to both create communities of discrete 3D microenvironments as well as to locally monitor subsequent divergent responses at both single cell and multi‐cell scales. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>